Key Concepts in Crime and Society - Coomber, Ross; Donnermeyer, Joseph F.; McElrath, Karen; Scott, John (SAGE Publications Ltd, 2014)
""A crucial text for whetting the academic appetite of those studying criminology at university. The comprehensive engagement with key crime and deviance debates and issues make this a perfect springboard for launching into the complex, diverse and exciting realm of researching criminology.""--Dr Ruth Penfold-Mounce, University of York""Essential reading for those new to the discipline and an invaluable reference point for those well versed in criminology and the sociology of crime and deviance.""--Dr Mark Monaghan, University of Leeds Key Concepts in Crime and Society offers an authoritative.
Keywords: kriminologie; kriminalita -- sociologické aspekty; criminology; crime -- sociological aspects; elektronické knihy; kolektivní monografie; electronic books; collective monographs